2014
DOI: 10.1007/s10157-014-0969-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p.E66Q variant of GLA in the progression of chronic kidney disease

Abstract: This study indicated that the p.E66Q variant of GLA does not affect the progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, seven patients had the p.Glu66Gln allele, which is known as a functional GLA variant [ 15 , 16 ] ( Table 1 ). The FD prevalence in patients with CKD Stage 5D was 0.06%, which corroborated the previous report [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, seven patients had the p.Glu66Gln allele, which is known as a functional GLA variant [ 15 , 16 ] ( Table 1 ). The FD prevalence in patients with CKD Stage 5D was 0.06%, which corroborated the previous report [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present cross-sectional study analyzed a subgroup of the Project in Sado for Total Health (PROST), a hospital-based cohort study in Sado City, Niigata Prefecture, Japan ( http://square.umin.ac.jp/prost/ ). The PROST began in June 2008 and is an ongoing cohort study targeting outpatients (age ≥20 years) of Sado General Hospital [ 21 ]. In the current study, 1,272 individuals registered with the PROST before November 19, 2012 were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In the present case, both PAS-positive vacuolated cardiomyocytes and small number of zebra bodies were observed in LV myocardium, but no accumulation of Gb3, indicating that those histological changes were not associated with Fabry disease. A recent study showed that the frequency of the E66Q allele was not different between hemodialysis patients and the general Japanese population [ 18 ]. Therefore, thorough genetic analysis is needed to perform differential diagnosis of Fabry disease.…”
Section: Case Presentationmentioning
confidence: 99%